2014
DOI: 10.1007/s11164-014-1728-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and anticancer activity of a new water-soluble derivative of heptaplatin, cis-{Pt(II)[(4R,5R)-4,5-bis(aminomethyl)-2-isopropyl-1,3-dioxolane](3-acetoxyl-cyclobutane-1,1-dicarboxylato)}

Abstract: A new water-soluble derivative of heptaplatin, cis-{Pt(II)[(4R,5R)-4,5bis(aminomethyl)-2-isopropyl-1,3-dioxolane](3-acetoxyl-cyclobutane-1,1-dicarboxylato)} has been synthesized, characterized by elemental analysis, MS, IR, and 1 H, 13 C NMR, and evaluated for in vitro anticancer activity in four human cancer cell lines. The stability of the derivative in water was also investigated by monitoring the changes of 1 H NMR in D 2 O. The results reveal that the new derivative has good solubility and stability in wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…In this study, two major compounds were identified in the methanol lutein-glycoside, and rutin as distinctive components in A. officinalis L. 21 It is well known that cyclobutane derivatives have antioxidant, anticancer, [51][52][53][54] and antimicrobial activities. 55,56 Moreover, propyl gallate and tert-butyl-hydroquinone have antioxidants and anticancer activities.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, two major compounds were identified in the methanol lutein-glycoside, and rutin as distinctive components in A. officinalis L. 21 It is well known that cyclobutane derivatives have antioxidant, anticancer, [51][52][53][54] and antimicrobial activities. 55,56 Moreover, propyl gallate and tert-butyl-hydroquinone have antioxidants and anticancer activities.…”
Section: Discussionmentioning
confidence: 99%